2016
DOI: 10.1016/j.ijepes.2015.12.022
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of topological properties of smart grids in power losses optimization problems

Abstract: Power losses reduction is one of the main targets for any electrical energy distribution company. In this paper, we face the problem of joint optimization of both network topology and distributed generator parameters in a real smart grid. We consider a portion of the Italian electric distribution network managed by the ACEA Distribuzione S.p.A. located in Rome, Italy. We perform both the power factor correction (PFC) for tuning the generators and the distributed feeder reconfiguration (DFR) to set the optimal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…A sensitivity analysis is also done on the planning costs and it is confirmed that the planning cost is highly sensitive to the energy price (for example, purchase and sale prices) 3 . In Possemato et al 4 the results show a reduction of energy losses due to the impact of Smart Grid. The reduction may seem insignificant, but the tests performed simulated only one hour of a specific day per year.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A sensitivity analysis is also done on the planning costs and it is confirmed that the planning cost is highly sensitive to the energy price (for example, purchase and sale prices) 3 . In Possemato et al 4 the results show a reduction of energy losses due to the impact of Smart Grid. The reduction may seem insignificant, but the tests performed simulated only one hour of a specific day per year.…”
Section: Discussionmentioning
confidence: 94%
“…Both long-term and short-term problems are mathematically formulated with mixed nonlinear programming and solved through PSO co-evolutionary (CPCE) culture. In Possemato et al 4 efforts are focused on optimizing the performance of active distribution networks through a reduction of losses. The main techniques used in the literature are the correction of the Power Factor (PF) and reconfiguration of the distribution grid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, graphs are commonly used to model a plethora of real-world, possibly complex, systems [ 1 ]. Notable examples include biological systems and chemistry [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], social and collaboration networks [ 14 ], computer vision and image processing [ 15 , 16 , 17 , 18 ], natural language processing [ 19 , 20 , 21 , 22 ], and energy distribution networks [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A graph representation for data is appropriate in several fields, including physics, chemistry, neuroscience, and sociology [1], where the phenomena under investigations can be observed as a sequence of measurements whose pairwise relationships are relevant too and thus included in the data representation [2]. In these application scenarios, the identification of a possible change in the system behavior, a situation associated with anomalies or events to be detected in the sequence, is of particular interest; examples of applications that can be cast in this framework are functional brain networks [3] and power grids [4]. Further relevant applications cover data acquired from cyber-physical systems and the Internet of Things [5].…”
Section: Introductionmentioning
confidence: 99%